2016
DOI: 10.1523/eneuro.0183-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Adult Conditional Knockout of PGC-1α Leads to Loss of Dopamine Neurons

Abstract: Visual AbstractParkinson's disease (PD) is a chronic progressive neurodegenerative disorder. Recent studies have implicated a role for peroxisome proliferator-activated receptor ␥ coactivator protein-1␣ (PGC-1␣) in PD and in animal or cellular models of PD. The role of PGC-1␣ in the function and survival of substantia nigra pars compacta (SNpc) dopamine neurons is not clear. Here we find that there are four different PGC-1␣ isoforms expressed in SH-SY5Y cells, and these four isoforms are expressed across subre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 30 publications
4
59
0
1
Order By: Relevance
“…PGC-1α activation of NRF1 leads to transcription of nuclear-encoded mitochondrial genes and of the mitochondrial DNA transcriptional factor Tfam, which activates transcription and replication of the mitochondrial genome, thereby controlling mitochondrial biogenesis ( Gleyzer et al, 2005 ; Koopman et al, 2010 ; Scarpulla et al, 2012 ; Ventura-Clapier et al, 2008 ). PGC-1α dysregulation and impaired mitochondrial biogenesis have been implicated in neurodegenerative disorders ( Calkins et al, 2011 ; Coppola et al, 2009 ; García-Giménez et al, 2011 ; Jiang et al, 2016 ; Johri et al, 2013 ; Marmolino et al, 2010 ; McGill and Beal, 2006 ; Reddy et al, 2012 ; Ruiz et al, 2012 ; Sandi et al, 2014 ; Shin et al, 2011 ; Stevens et al, 2015 ; Thau et al, 2012 ). Downregulation of PGC-1α mRNA and protein have been reported in skeletal muscle, fibroblasts and neural precursor cells cultured from FRDA patients and animal models ( Coppola et al, 2009 ; Marmolino et al, 2010 ; Sandi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1α activation of NRF1 leads to transcription of nuclear-encoded mitochondrial genes and of the mitochondrial DNA transcriptional factor Tfam, which activates transcription and replication of the mitochondrial genome, thereby controlling mitochondrial biogenesis ( Gleyzer et al, 2005 ; Koopman et al, 2010 ; Scarpulla et al, 2012 ; Ventura-Clapier et al, 2008 ). PGC-1α dysregulation and impaired mitochondrial biogenesis have been implicated in neurodegenerative disorders ( Calkins et al, 2011 ; Coppola et al, 2009 ; García-Giménez et al, 2011 ; Jiang et al, 2016 ; Johri et al, 2013 ; Marmolino et al, 2010 ; McGill and Beal, 2006 ; Reddy et al, 2012 ; Ruiz et al, 2012 ; Sandi et al, 2014 ; Shin et al, 2011 ; Stevens et al, 2015 ; Thau et al, 2012 ). Downregulation of PGC-1α mRNA and protein have been reported in skeletal muscle, fibroblasts and neural precursor cells cultured from FRDA patients and animal models ( Coppola et al, 2009 ; Marmolino et al, 2010 ; Sandi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has demonstrated that adult conditional PGC-1α KO mice display a significant loss of DA neurons in the SNpc (Jiang et al, 2016). Taken together with PGC-1α overexpression data, which has been shown to rescue mitochondrial biogenesis defects and accompanying neurodegeneration, it stands to reason that finding compounds which upregulate PGC-1α expression may be therapeutically beneficial.…”
Section: Therapeuticsmentioning
confidence: 99%
“…PARIS (ZNF746) is a pathologic parkin substrate, which is increased in sporadic and familial PD brains and is responsible for DA neuronal loss in mouse models of parkin inactivation (Shin et al, 2011; Siddiqui et al, 2015; Siddiqui et al, 2016; Stevens et al, 2015). PARIS accumulation represses the transcriptional coactivator, peroxisome proliferator-activated receptor gamma coactivator-1-alpha (PGC-1α), which is critical for DA neuron survival (Ciron et al, 2015; Jiang et al, 2016; Mudo et al, 2012; Zheng et al, 2010). …”
Section: Introductionmentioning
confidence: 99%